Comment on "Aqueous SET-LRP catalyzed with in situ generated Cu(0) demonstrates surface mediated activation and bimolecular termination" by S. Samanta, et al., Polym. Chem., 2015, 6, 20841. Issue 22 (14th June 2015) - Harrisson, S.
<x xml:space="preserve">Abstract</x> A recent paper proposed a new polymerization mechanism for aqueous SET-LRP, but experimental results are consistent with conventional radical propagation and termination.